2022
DOI: 10.3171/2022.7.focus22338
|View full text |Cite
|
Sign up to set email alerts
|

Racial and socioeconomic disparities in the advanced treatment of medically intractable pediatric epilepsy

Abstract: OBJECTIVE Racial and ethnic disparities in healthcare have gained significant importance since the Institute of Medicine published its report on disparities in healthcare. There is a lack of evidence on how race and ethnicity affect access to advanced treatment of pediatric medically intractable epilepsy. In this context, the authors analyzed the latest Kids’ Inpatient Database (KID) for racial/ethnic disparities in access to surgical treatment of epilepsy. METHODS The authors queried the KID for the years 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Another and even more important caveat is the risk of increasing social and racial disparities that are well documented in epilepsy. [125] , [126] , [127] By training on data that contain these bias, researchers must take active steps to identify and correct for these inequities. [128] , [129] Simulation studies could help quantify the net clinical benefits and provide an accurate cost-benefits estimate, [130] which will ultimately hinge on the diagnostic performances of the algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Another and even more important caveat is the risk of increasing social and racial disparities that are well documented in epilepsy. [125] , [126] , [127] By training on data that contain these bias, researchers must take active steps to identify and correct for these inequities. [128] , [129] Simulation studies could help quantify the net clinical benefits and provide an accurate cost-benefits estimate, [130] which will ultimately hinge on the diagnostic performances of the algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…The financial implications impacts the access to these treatments. Studies have documented disparities in access to neurosurgical treatments in other patient populations 57,58 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented disparities in access to neurosurgical treatments in other patient populations. 57,58 Extrapolating existing cost-effectiveness studies focused on these treatment modalities may be required, as cost-effectiveness analyses specific to GA1 are lacking. Newborn screening for GA1 is cost-effective.…”
Section: Implications For Clinical Decisionmaking and Patient Educationmentioning
confidence: 99%
“…Even if one exists, it is essential to understand why the refusal rates were linked to race or cultural beliefs. Implicit bias of physicians while discussing the treatment options is one of the undeniable factors which can contribute to some of these disparities 5 18. Several studies have reported that minority groups were less likely to accept surgical recommendations across several surgical specialties.…”
Section: Discussionmentioning
confidence: 99%